Combination of methylprednisolone pulse therapy and remission inducing drugs in rheumatoid arthritis. Issue 4 (April 1987) - Hansen, T M; Dickmeiss, E; Jans, H; Ingemann Hansen, T; Ingeman-Nielsen, M; Lorenzen, I
Abstract : Thirty patients with rheumatoid arthritis were allocated to either methylprednisolone pulse therapy or placebo at the beginning of treatment with either gold salts, penicillamine, or azathioprine. Methylprednisolone pulse therapy produced an immediate but temporary anti-inflammatory effect lasting for a maximum of four to eight weeks. It also caused a lasting depression of serum IgG, but no effect was observed on the proportion of T and B lymphocytes, proliferative responses, or on concanavalin A induced suppressor cell activity, and there was no effect on the amount of circulating immune complexes. The bone mineral content decreased similarly in the two groups, and methylprednisolone pulses had no effect on the progression of erosions on x rays during an observation period of eight months. A single pulse of methylprednisolone can give a short lasting anti-inflammatory effect but is of little or no value in the long term treatment of rheumatoid arthritis.